Melody and poetry are two wings of aesthetics (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article talks about aesthetics, a phenomenon that gives color, color, and shape to the entire civilized world. The relevance of aesthetics and melody is considered, and this is what modern poetry needs. The research method considered was the study of whether poetry created by women differs from poetry created by gentlemen. As a result, in women’s poetry, the lyrics are strong and consist of invocative voices that sound for the Motherland. It was also said that the women also showed that the civilization built by the Chinese is a great civilization.
Keywords: aesthetics, civilization, architecture, modern lyrics, contribution